Effective Leadership Towards Patient Safety Management At Unimus Hospital - Tri Hartiti; Arief Yanto; Hanik Zahro Nabila (Media Keperawatan Indonesia, 2025)
Patient safety management is a fundamental indicator of hospital quality and reflects the effectiveness of healthcare service delivery. Effective leadership plays a critical role in fostering a patient safety culture, minimizing risks, preventing adverse events, and improving the quality of nursing care. This study aimed to examine the relationship between effective leadership and patient safety management at Universitas Muhammadiyah Semarang Hospital. A quantitative cross-sectional study was conducted involving 50 nurses working at the hospital. Data were collected using structured questionnaires assessing perceptions of effective leadership and patient safety implementation. Descriptive statistics and Pearson Product-Moment correlation analysis were used to analyze the data. The findings revealed that most respondents were female (82%) and held a diploma in nursing (54%), while 46% had a professional nursing degree. The mean age of respondents was 26.97 ± 6.78 years, and the mean work experience was 1.98 ± 3.62 years. Nurses perceived leadership effectiveness at the hospital to be high, with a mean score of 103 ± 13.54. In terms of patient safety management, 84% of respondents demonstrated good implementation of patient safety practices. Statistical analysis showed a significant positive correlation between effective leadership and patient safety management (r = 0.457, p = 0.001), indicating that stronger leadership effectiveness was associated with better implementation of patient safety practices. In conclusion, effective leadership is significantly associated with improved patient safety management in hospital settings. Strengthening leadership capacity may contribute to the development of a stronger patient safety culture and enhance the quality of healthcare services.